Virtual Reality-Supported Drilling Strategy In Teaching English Vocabulary To Young Learners - Halimah Halimah; Vina Nurviyani; Asep Saepulah; Jauhar Helmie; Rahmi Wulandari Wandawati; Siti Mutiah (Universitas Muhammadiyah Kalimantan Timur, 2022)
This present research intent to discover the implementation of Virtual Reality (VR) media in supporting drilling strategy to teach English vocabulary to young learners modeled by a current teacher who is taking Independent Learning-Campus Merdeka (Merdeka Belajar-Kampus Merdeka or MBKM) as the participant of this study. She is holding a responsibility to teach English lesson to a school partnership. The school that is in partnership is Trikarya Public Elementary School of Cipanas district. This research collected the data through observation on teaching praxis using VR media. As the data were collected, the writer analyzed them. There were six steps in analyzing the data; (1) preparing the data to be analyzed, (2) reading or viewing all data, (3) coding the data, (4) generalizing the code, (5) creating tables based on the data code, and (6) interpret the data code. Over the observation the writers found a new procedure on implementing VR media in teaching English vocabulary to elementary students. There are three stages in this procedure that is called PMP. PMP stands for Pre-Activity, Main Activity, and Post-Activity. Furthermore, there are four activities in the main stage; Watch, Collect, Sharing, and Practice and hereafter is called WCSP. The last finding uncovers that the teacher is using drilling as the teaching strategy to activate the students.